Characterization of fatal road traffic accidents using K-means clustering: a case study of Bogotá (2010)
This paper aims at analyzing which are the characteristics of the fatal road accidents occurring in Bogotá in 2008 by using the Algorithm K-means in order to identify accident circumstances that frequently occur together. Results show that two pair of interactions characterize most of fatal road accidents: Public Transport-Pedestrians and Public Transport-Motorcycle. These exploratory results show the potentiality of the clustering techniques in order to identify specific combinations of relevant variables that will give hints for a better road safety program.